2006
DOI: 10.1002/jmri.20527
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial tagging and strain analysis at 3 Tesla: Comparison with 1.5 Tesla imaging

Abstract: Purpose: To determine whether imaging at 3 T could improve and prolong the tag contrast compared to images acquired at 1.5 T in normal volunteers, and whether such improvement would translate into the ability to perform strain measurements in diastole. Materials and Methods:Normal volunteers (N ϭ 13) were scanned at 1.5 T (GE Signa CV/i) and 3.0 T (GE VH/i). An ECG-triggered, segmented k-space, spoiled-gradient-echo grid-tagged sequence was used during cine acquisition. Tag contrast was determined by the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 15 publications
4
40
0
Order By: Relevance
“…Nevertheless, these studies also showed an improvement when using 3T compared to 1.5T, as reported by an 80% increase in tagging CNR [4]. Regional variations across the left ventricle of 50% higher end systolic tagging CNR at 3T for an anterior region compared to an inferior region were also reported previously [6].…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…Nevertheless, these studies also showed an improvement when using 3T compared to 1.5T, as reported by an 80% increase in tagging CNR [4]. Regional variations across the left ventricle of 50% higher end systolic tagging CNR at 3T for an anterior region compared to an inferior region were also reported previously [6].…”
Section: Resultssupporting
confidence: 56%
“…Noise in tagging MRI at 1.5T and 3T has been studied before [4,6,7]. Pulse sequence wise, DENSE and tagging MRI based on 1-1 SPAtially Modulated Magnetization (SPAMM) are closely related [17], and the results found in this study should be transferable to the regime of tagging analyzed with HARP.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Markl et al26 ( n = 16) compared image quality using tagging at both field strengths and reported an increase in off‐resonance artifact at 3.0T, without an effect on overall image quality. Kramer et al27 ( n = 14) and Valeti et al28 ( n = 13) reported better image quality with tagging at 3.0T.…”
Section: Discussionmentioning
confidence: 95%